2017
DOI: 10.1007/978-94-024-1225-3_19
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Solar Wind–Magnetosphere–Ionosphere–Atmosphere Coupling and the Generation of Magnetospheric Currents

Abstract: We review the morphology and dynamics of the electrical current systems of the terrestrial magnetosphere and ionosphere. Observations from the Active Magnetosphere and Planetary Electrodynamics Response Experiment (AMPERE) over the three years 2010 to 2012 are employed to illustrate the variability of the field-aligned currents that couple the magnetosphere and ionosphere, on timescales from minutes to years, in response to the impact of solar wind disturbances on the magnetosphere and changes in the level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 87 publications
3
24
0
Order By: Relevance
“…10.1029/2019GL082824 (SCW), and (C) westward electrojet. Whereas B is associated with the SCW, or DP1 perturbations, A and C can be related to the general magnetospheric convective system, DP2 (Nishida, 1968), which is enhanced during substorm growth and expansion phases (Milan et al, 2017). To summarize the above results, we identify key time ranges, before and after onset: 0 ≤ t1 ′ < 10, 10 ≤ t2 ′ < 20, 20 ≤ t3 ′ < 30 and t4 ′ ≥ 30 in terms of normalized time, t ′ .…”
Section: Geophysical Research Lettersmentioning
confidence: 99%
“…10.1029/2019GL082824 (SCW), and (C) westward electrojet. Whereas B is associated with the SCW, or DP1 perturbations, A and C can be related to the general magnetospheric convective system, DP2 (Nishida, 1968), which is enhanced during substorm growth and expansion phases (Milan et al, 2017). To summarize the above results, we identify key time ranges, before and after onset: 0 ≤ t1 ′ < 10, 10 ≤ t2 ′ < 20, 20 ≤ t3 ′ < 30 and t4 ′ ≥ 30 in terms of normalized time, t ′ .…”
Section: Geophysical Research Lettersmentioning
confidence: 99%
“…Flow shears in this convection pattern are associated with the divergence of electric field and Pedersen current in the ionosphere and the corresponding FACs sensed by AMPERE. Auroras produced by precipitating electrons carrying upward FACs move to lower and higher latitudes as the polar cap expands and contracts, as described by the expanding and contracting polar cap (ECPC) model (Clausen et al, 2012;Cowley & Lockwood, 1992;Milan et al, 2003Milan et al, , 2007Milan et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of the current study was to determine some properties of the electrical conductivity parallel to the geomagnetic field in the ionosphere at Swarm altitude. When considering climatological conductivity maps based on 4 years of observations we found that: Two conductivity maxima occur: one at very high QD latitudes (at 80°) around noon and one at low latitudes (within ±20°) at dawn; which may be associated to the R1 and the cusp region (Milan et al., 2017) and the morning overshoot (Stolle et al., 2011), respectively There is an evident and expected conductivity asymmetry from day to night. In the dayside the effect of solar EUV is dominant and conductivity has a peak at 15:00 MLT and at ±50° QD latitude.…”
Section: Discussionmentioning
confidence: 88%
“…Here, the electrical conductivity for both Northern (left) and Southern (right) Hemispheres saturated between 2.5 and 5.0×normal10110.3333emnormals1 is reported in the first row. The conductivity ranges between 2.1 and 6×normal10110.3333emnormals1, has a maximum error (computed as explained above) of 0.6%, and is characterized by the existence of two maxima: at very high latitudes (around ±normal80°) between 09:00 and 12:00 MLT, in correspondence with the Region R0 and the polar magnetic cusp (Milan et al., 2017), and at low latitudes (within ±normal20°) around 06:00 MLT. The latter peak, which represents the absolute maximum value of σfalse‖, corresponds to the morning overshoot (Stolle et al., 2011).…”
Section: Resultsmentioning
confidence: 99%